Infrastructure Status and Future Requirements of Periodical Markets in Odisha - Gummagolmath, KC; Singh, Shalendra; Sharma, P (Journal of Agricultural Extension Management, 2019)
The present study was conducted to know gaps in infrastructure of Gram Panchayat markets in Odisha and to suggest measures for improvement in the functioning of these markets. Markets selected for the study were grouped into two categories viz., small and big markets based on quantum of arrivals and number of users. Findings of the study revealed that arrivals of all the agricultural produce were four to five times higher in big markets as compared to small markets, except in case of arrivals of oilseeds and fruits. Similarly, the number of vehicles arriving during market days were also on the higher side for big markets. Among the users, on an average, 1823 and 3560 farmers visited small and big markets respectively. The study also analysed the gaps in infrastructure requirement in these markets in terms of utilities for the convenience of the consumers etc. Budget estimates for providing these infrastructures was on an average, Rs. 90.14 lakhs for large markets and Rs.33.45 lakhs for small markets. The targeted improvement of activities is suggested based on the gaps in core infrastructure such as cover shed, drying platform, cleaning and grading facilities etc. Provision of services, facilities and outlets for the improved collection, market preparation, transportation and sale of agricultural produce is also suggested. The study suggested that in order to achieve the goal of providing Good Marketing Practices in periodical markets, Regulated Market Committees should take over the ownership and maintenance of markets. As per the budget provisions made in the 13th Finance Commission, the average budget earmarked for developing each market amounts to Rs.40 lakhs. In view of this, the small markets fall within this prescribed budget and hence may be developed solely using the funds from the Commission. For large markets, additional budget may be provided by State Marketing Board or Department of Agricultural Marketing.